Analisis Risiko Produksi Pertanian Mentimun pada Lahan Gambut di Kubu Raya - Zusnita Anggraini; Eva Dolorosa; Wanti Fitrianti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Kubu Raya Regency, particularly Rasau Jaya District, is a region in West Kalimantan dominated by peatlands. One of the leading agricultural products in this area is cucumber. However, cucumber production in Rasau Jaya District experiences significant annual fluctuations. These fluctuations are caused by various risks, such as vulnerability to climate change, which triggers pest and plant disease outbreaks, and physical and chemical damage to peatlands. This study, conducted in 2023, aims to describe cucumber production outcomes, analyze factors affecting production risks, and measure the magnitude of those risks. Data were collected from 30 respondents who are cucumber farmers in Rasau Jaya District. The research highlights that peatlands, while fertile, are highly sensitive to environmental changes, making risk management crucial for sustainable agriculture. Farmers face challenges such as limited access to agricultural inputs and unpredictable weather conditions, further amplifying the risks in cucumber farming. The socio-economic characteristics of respondents, including education levels and farming experience, also play a role in managing production risks. Data analysis was performed using the coefficient of variation (CV) method and multiple linear regression. The results show that the production risk of cucumber farming in peatlands has a CV value of 0.009, indicating a low risk (CV < 0.5). The analyzed factors include land area, seeds, labor, lime usage, and poles and strings. These factors significantly influence the production risks of cucumbers in the area. This study provides insights into the conditions and risks of cucumber cultivation in the peatlands of Rasau Jaya. The information obtained can serve as a basis for better risk management in peatland agricultural practices.